3D Spheroids of Umbilical Cord Blood MSC-Derived Schwann Cells Promote Peripheral Nerve Regeneration - Lin, Yu-Jie; Lee, Yun-Wei; Chang, Che-Wei; Huang, Chieh-Cheng (Frontiers in Cell and Developmental Biology, 2020)
Schwann cells (SCs) are promising candidates for cell therapy due to their ability to promote peripheral nerve regeneration. However, SC-based therapies are hindered by the lack of a clinically renewable source of SCs. In this study, using a well-defined nongenetic approach, umbilical cord blood mesenchymal stem cells (cbMSCs), a clinically applicable cell type, were phenotypically, epigenetically, and functionally converted into SC-like cells (SCLCs) that stimulated effective sprouting of neuritic processes from neuronal cells. To further enhance their therapeutic capability, the cbMSC-derived SCLCs were assembled into three-dimensional (3D) cell spheroids by using a methylcellulose hydrogel system. The cell–cell and cell–extracellular matrix interactions were well preserved within the formed 3D SCLC spheroids, and marked increases in neurotrophic, proangiogenic and anti-apoptotic factors were detected compared with cells that were harvested using conventional trypsin-based methods, demonstrating the superior advantage of SCLCs assembled into 3D spheroids. Transplantation of 3D SCLC spheroids into crush-injured rat sciatic nerves effectively promoted the recovery of motor function and enhanced nerve structure regeneration. In summary, by simply assembling cells into a 3D-spheroid conformation, the therapeutic potential of SCLCs derived from clinically available cbMSCs for promoting nerve regeneration was enhanced significantly. Thus, these cells hold great potential for translation to clinical applications for treating peripheral nerve injury.